Seven Generations of Iroquois Leadership : The Six Nations since 1800 - Hauptman, Laurence M. (Book collections on Project MUSE., 2008)
"In Seven Generations of Iroquois Leadership, Laurence M. Hauptman traces the past 200 years of the Six Nations⁰́₉ history through the lens of the remarkable leaders who shaped it."